1999
DOI: 10.1089/088922299309847
|View full text |Cite
|
Sign up to set email alerts
|

T Cell-Derived Suppressive Activity: Evidence of Autocrine Noncytolytic Control of HIV Type 1 Transcription and Replication

Abstract: The ability of CD8+ T lymphocytes to suppress the transcription and replication of HIV-1 is well documented. We have demonstrated that the factor(s) responsible for the suppression of HIV-1 LTR-mediated gene expression are not the CC chemokines RANTES, MIP-1alpha, and MIP-1beta. Interestingly, these and other chemokines and cytokines are produced by both CD8+ and CD4+ T lymphocytes. On the presumption that CD4+ T lymphocytes may also be able to modulate HIV-1 expression in vitro we assessed the LTR-modulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Here, we have identified that IL-27 is a novel antiviral cytokine. A number of soluble anti-HIV factors have been identified from tissue culture supernatants, [11][12][13][14][15] and it has been proposed that HIV replication might be immunologically controlled by soluble factors. 65 Understanding the mechanism of IL-27-mediated HIV inhibition may delineate an invaluable insight into immunologic control of HIV replication and possible strategies for therapeutic invention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we have identified that IL-27 is a novel antiviral cytokine. A number of soluble anti-HIV factors have been identified from tissue culture supernatants, [11][12][13][14][15] and it has been proposed that HIV replication might be immunologically controlled by soluble factors. 65 Understanding the mechanism of IL-27-mediated HIV inhibition may delineate an invaluable insight into immunologic control of HIV replication and possible strategies for therapeutic invention.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15] For example, secretion of anti-HIV ␤-chemokines and CD8 antiviral factor (CAF) from human T-lymphotropic virus (HTLV)-type 1 and herpes virus saimiri-infected cell line have been described. [11][12][13][14][15] Although a combination of antibodies and suppressive factors was able to reverse the inhibitory activity of CAF, complete reversal of HIV-1 suppression was not observed, suggesting that additional unknown suppressive factors were involved. 16 Certain microbial organisms elicit immune responses that reduce clinical HIV-1 infection presumably through the induction of soluble suppressive factors.…”
mentioning
confidence: 99%
“…Although much of this interest was dedicated to studying the antiviral responses of CD8 T lymphocytes, it has been well known that some infected individuals mount vigorous HIV-1-specific CD4 T cells responses, resulting in the elaboration of IFN-␥ and antiviral ␤-chemokines (12). Furthermore, a number of studies suggested that CD4 T cells mediated the secretion of unidentified protein factor(s), acting after virus entry to restrict virus replication (10,(13)(14)(15).…”
mentioning
confidence: 99%
“…However, several studies have shown that these ␤-chemokines cannot entirely account for CAF-mediated antiviral effects, particularly since CAF can inhibit the replication of HIV-1 strains that use CXCR4 and not CCR5 for entry (1,20,28,29,36). Furthermore, CAF can prevent HIV-1 replication postentry (6,10,23,25,29,41). In addition to the ␤-chemokines, a number of other soluble factors including interleukin-16, interferons, macrophage-derived chemokines, antithrombin III, and most recently ␣-defensins 1 to 3, may contribute to CAF activities (17,49; reviewed in reference 40).…”
mentioning
confidence: 99%
“…Several independent reports have shown that CAF can inhibit HIV-1 RNA transcription, particularly at the step of long terminal repeat (LTR)-driven gene expression (6,10,23,25), although this is not the only step in the virus life cycle inhibited by CAF. Previously, we demonstrated that CAF inhibits HIV-1 replication and LTR activation through activation of STAT1 (signal transducers and activators of transcription) (3).…”
mentioning
confidence: 99%